2016
DOI: 10.1099/jgv.0.000400
|View full text |Cite
|
Sign up to set email alerts
|

Inter-segment complementarity in orbiviruses: a driver for co-ordinated genome packaging in the Reoviridae?

Abstract: The process by which eukaryotic viruses with segmented genomes select a complete set of genome segments for packaging into progeny virus particles is not understood. In this study a model based on the association of genome segments through specific RNA-RNA interactions driven by base pairing was formalized and tested in the Orbivirus genus of the Reoviridae family. A strategy combining screening of the genomic sequences for inter-segment complementarity with direct functional testing of inter-segment RNA-RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 51 publications
4
31
1
Order By: Relevance
“…The co-evolving pair of complementary nucleotide sequences between S5 and S10 identified in the present study corresponded to one of two putative bundling signals reported in the previous experimental study mentioned above (Boyce et al, 2016). This observation validates the effectiveness of the strategy of identifying coevolving pairs of complementary nucleotide sequences as candidates for bundling signals in viruses with segmented genomes (Suzuki, 2014(Suzuki, , 2015.…”
supporting
confidence: 72%
See 4 more Smart Citations
“…The co-evolving pair of complementary nucleotide sequences between S5 and S10 identified in the present study corresponded to one of two putative bundling signals reported in the previous experimental study mentioned above (Boyce et al, 2016). This observation validates the effectiveness of the strategy of identifying coevolving pairs of complementary nucleotide sequences as candidates for bundling signals in viruses with segmented genomes (Suzuki, 2014(Suzuki, , 2015.…”
supporting
confidence: 72%
“…It has been reported that a pair of nucleotide sequences consisting of 6-11 bases located in the 5' end of the open reading frame (ORF) of S1 and in the 3' untranslated region (UTR) of S7, and also a pair of nucleotide sequences consisting of 6-8 bases located in the 5' UTR of S5 and in the 3' UTR of S10, were both complementary in each of 15 Orbivirus species, although the length and the absolute sequence of these complementary nucleotide sites varied among the species (Boyce et al, 2016). By predicting the intramolecular secondary structures for + RNAs of these segments in each species, the sites identified in S7 and S10 were inferred to be located in loops at the end of stable stems, whereas those identified in S1 and S5 were inferred to be located in regions of low base pairing (Boyce and McCrae, 2015;Boyce et al, 2016).…”
mentioning
confidence: 99%
See 3 more Smart Citations